2016
DOI: 10.23939/chcht10.04.437
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Determination of Oil and Grease Contents in Wastewater from the Petroleum Industry

Abstract: Abstract. Infrared spectrometry and spectrofluorimetry methods were correlated in the measurement of oil concentration in produced water. Furthermore, we compared colorimetry and gravimetry techniques. Adsorption experiments were performed in synthetic oily wastewaters by polymer compounds based on poly(hydroxyethyl acrylamide and polypropylene. The residual oil content was used in the techniques correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…The oil content in the samples was determined using a spectrophotometer following the methods described by Cirne et al [ 25 ]. For such, a calibration curve was created for different concentrations of oil in n-hexane.…”
Section: Methodsmentioning
confidence: 99%
“…The oil content in the samples was determined using a spectrophotometer following the methods described by Cirne et al [ 25 ]. For such, a calibration curve was created for different concentrations of oil in n-hexane.…”
Section: Methodsmentioning
confidence: 99%
“…Parameters such as chemical oxygen demand, total suspended solid (TSS), and volatile suspended solid (VSS) were analyzed according to the standard method for the Examination of Water and Wastewater APHA [25]. Fats, oil, and grease content were analyzed following the procedure reported by Cirne et al [26]. However, TSS samples were filtered through a 0.47 µm filter paper placed on a vacuum pump before the examination.…”
Section: Methodsmentioning
confidence: 99%
“…50−54 Nevertheless, it must be considered that the emission intensity of samples with complex composition, such as crude oils, will depend on the amount of molecules that can be excited, for example, aromatics, alkyl-aromatics, and polyacromatic hydrocarbons (PAHs), requiring calibration curves for each kind of oil. 32 A previous work 55 demonstrated that different techniques to determine TOG provide different results which depends on the type of oil and the oil concentration in water. Although the work has used a wide spectrum of methods (fluorimetry, gravimetry, colorimetry, and infrared spectrometry), only two theoretical oil concentrations were evaluated (40 and 120 ppm), and the differences in the three crude oils studied were not reported.…”
Section: T H Imentioning
confidence: 99%